Large variability of frequency and type of physical therapy in patients of the German Network for Systemic Sclerosis - Belz, Doreen; Moinzadeh, P.; Riemekasten, G.; Henes, J.; Müller‐Ladner, U.; Blank, Norbert; Koetter, I.; Siegert, E.; Pfeiffer, C.; Schmalzing, M.; Zeidler, G.; Schmeiser, T.; et al. (Arthritis care & research, 2020)
Objectives To determine the type and frequency of physical therapy (PT) prescribed by physicians to patients of the registry of the German Network for Systemic Sclerosis. Methods The data of 4252 patients were analysed using descriptive statistics, chi-squared tests and odds ratios. Results Overall, 37.4% (n=1590 / 4252) of the patients received PT at the end of yearly follow-up. The most frequently used type of PT was lymphatic drainage (36.8% / n=1061), followed by exercise therapy (36.3% / n=1047) and heat therapy (23.9% / n=689). More than three quarters of treated patients (82%) received one or two different forms of PT simultaneously. The prescription of PT was associated with the extent of skin fibrosis as measured by modified Rodnan Skin Score (mRSS) (mRSS<10: 41.8% / mRSS 11-20: 55.8% / mRSS>21: 63.9%; p<0.001). Patients with musculoskeletal involvement (arthritis, muscle weakness, joint contractures, tendon friction rubs, e.g.) had a higher chance to receive PT than patients without these symptoms, with corresponding odds ratios ranging from 1.96 (95% CI 1.69-2.28; for joint contractures) to 3.83 (95% CI 2.89-5.08; for arthritis). Comparing the type of PT prescription across the initial and all follow-up visits from 2003-2017, significant alterations with a decreasing frequency of patients receiving PT could be observed (p=0,001). Conclusions This is the first study reporting the use of physical therapy in SSc patients in a large cohort. Although SSc is characterized by considerable disability and restriction of motion, less than 40% of patients received PT. This article is protected by copyright. All rights reserved.
First published: 31 May 2019
peer review
Gesehen am 30.10.2020